Manure nutrient application on a Chinese dairy farm with arable land: A case study based on Dutch experience of equilibrium fertilization - Melse, Roland W.; de Buisonjé, Fridtjof E.; Wei, Qiao; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2017)
For a Chinese dairy farm with 2200 milking cows, the annual manure production and manure nutrients (nitrogen and phosphorus) were estimated. Gaseous nitrogen losses from cattle housing with scraped solid floors were based on on-farm measurements. Based on experiences from the Netherlands, nutrient levels in the solid and liquid fractions after slurry separation were estimated. On the basis of assumptions for nutrient losses during covered lagoon storage and land application of the liquid fraction, nitrogen and phosphorous fertilization rates were calculated for the 67 hm2 of agricultural land that receive the liquid fraction by gravity irrigation. The results show that the application rates of nitrogen and phosphorous significantly exceed the crop needs, which will probably result in losses to soil and water. In order to aim for a balance between nutrient application and crop needs and, as such, reduce environmental harm, the authors recommend to establish application standards for nitrogen and phosphorous on arable land in China and to formulate farm-specific Nutrient Management Plans. Keywords: dairy manure, nutrient balance, dairy farm, over-fertilization, nutrient application standard, environmental protection DOI: 10.25165/j.ijabe.20171004.3082 Citation: Melse R W, de Buisonjé F E, Qiao W, Dong R J. Manure nutrient application on a Chinese dairy farm with arable land: A case study based on Dutch experience of equilibrium fertilization. Int J Agric & Biol Eng, 2017; 10(4): 182–188.